Kajian Biblika Tentang Makna Frasa Bertolong-Tolonglah Menanggung Bebanmu Berdasarkan Galatia 6:1-5 dan Implikasinya Bagi Orang Percaya Masa Kini - Lolongan, Renard; Luthy, Christopher James; F. Dju, Nyoman Lisias; Lele, Aldorio Flavius (Jurnal Kala Nea, 2020)
The purpose of writing this thesis is to find out the meaning of the phrase “help bear your burdens,” based on Galatians 6:1-5. The research method used is a qualitative research method with inductive reasoning, using an exegesis approach through the application of the principles and methods of Biblical Hermeneutics by Hasan Sutanto. After doing the research, the writer came to the following conclusions: First, the meaning of the phrase help bear your burdens is a form of command to believers who accidentally slip into a violation because they take the wrong step in his faith. Fellowship of believers must help bear the heavy burdens of fellow transgressors, so that he has greater and faster opportunites to recover from his transgressions (6:1b), so that in the end he returns to true faith and experiences spiritual growth in Jesus Christ. Second, the meaning of the phrase help bear your burdens states that Paul’s command in verse 2a and his statement in verse 5, do not contradict each other. Third, the meaning of the phrase help bear your burdens reveals God’s truth about the call of life for believers to bear two kinds of burdens in life. The first burden is a burden that must be borne together as a community, because it is very burdensome and cannot be borne alone (6:2a). Then the second burden is the work of service that God has given to each believer to bear (6:5).